Stereoscopy in Surgical Neuroanatomy: Past, Present, and Future. Issue 2 (19th June 2019) - Rubio, Roberto Rodriguez; Bonaventura, Rina Di; Kournoutas, Ioannis; Barakat, Dania; Vigo, Vera; El-Sayed, Ivan; Abla, Adib A
Abstract: Since the dawn of antiquity, scientists, philosophers, and artists have pondered the nature of optical stereopsis—the perception of depth that arises from binocular vision. The early 19th century saw the advent of stereoscopes, devices that could replicate stereopsis by producing a 3D illusion from the super-imposition of 2D photographs. This phenomenon opened up a plethora of possibilities through its usefulness as an educational tool—particularly in medicine. Before long, photographers, anatomists, and physicians were collaborating to create some of the first stereoscopic atlases available for the teaching of medical students and residents. In fields like neurosurgery—where a comprehensive visuospatial understanding of neuro-anatomical correlates is crucial—research into stereoscopic modalities are of fundamental importance. Already, medical institutions all over the world are capitalizing on new and immersive technologies—such as 3D intraoperative recording, and 3D endoscopes—to refine their pedagogical efforts as well as improve their clinical capacities. The present paper surveys the history of stereoscopy from antiquity to the modern era—with a focus on its role in neurosurgery and medical education. Through the tracking of this evolution, we can discuss potential benefits, future directions, and highlight areas in which further research is needed. By anticipating these factors, we may strive to take full advantage of an emergent field of technology, for our ultimate goal of improving patient care.